The Effectiveness of the World Health Organization (WHO) in Overcoming the Covid 19 Pandemic - Hilton Tarnama PM; Belardo Prasetya Mega Jaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The Covid 19 outbreak has caused a lot of casualties. WHO as an international organization whose goal is to achieve health at the highest level has a responsibility to mitigate the spread of the virus and its victims. The authority possessed by WHO based on international law is effective in overcoming the covid 19 pandemic. All of the categorizations to assess the effectiveness of WHO can be fulfilled by WHO while showing that WHO has succeeded in overcoming the Covid 19 pandemic.